WITNESS PROTECTION IN INDIA: LAWS AND PRACTICE - Tiwari, Abhishek Kumar; Singh, Veer Vikram; Srivastava, Deepmala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Judicial systems worldwide, whether dealing with criminal or civil matters, are designed to achieve justice through established laws and procedures. Witnesses play a crucial role in trial proceedings by providing evidence. In India, this holds true, with trials heavily reliant on witness testimony to establish facts. However, witness protection laws and practices are still in a developmental stage. The author undertakes an analysis of witness protection in India, examining the laws, practices, and procedures within the judicial system and legislature